Sme acceptance on Islamic SME financing, an overview from Islamic banking attributes - Ahmad Aizuddin Hamzah; Norhazlina Ibrahim; Amir Shaharuddin; Sumaiyyah Abd Aziz (Faculty of Economics and Muamalat, Universiti Sains Islam Malaysia, 2024)
This paper aims to integrate the theory of planned behavior—focusing on the variables of attitude, subjective norm, and perceived behavioral control—with the concept of Islamic banking attributes, including access to Islamic finance and product range. By doing so, it proposes a conceptual framework to determine the preferences for Islamic SME financing. The framework formulation is based on a comprehensive review of literature related to SME financing behavior and Islamic banking acceptance. This paper addresses the critical issue of inadequate financing faced by SMEs, which significantly hampers their growth potential. By identifying the existing gap in Islamic SME financing and proposing a framework to understand these preferences, this study contributes to the literature. The findings of this research will not only assist entrepreneurs in identifying alternative and reliable sources of financing to achieve their growth objectives but will also aid policymakers and other stakeholders in enhancing the lending infrastructure and related technologies for SME financing.